PENGARUH FINANCIAL DISTRESS TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Property and Real Estate yang Terdaftar dalam Bursa Efek Indonesia (BEI) Periode Tahun 2016-2020 ) - Tina Tri Kusumawati; Antonius Mulyo Haryanto (Diponegoro Journal of Management, 2022)
This study aims to empirically examine the effect of financial distress on firm value in property and real estate companies listed on the Indonesia Stock Exchange (IDX), the period from 2016 to 2020. In this study, two financial distress prediction models are used, namely the Altman Z-score prediction model. and the Zmijewski X-score prediction model to be used as a predictor variable on firm value which is reflected in the price book value. Signal theory and agency theory serve as the basis for the conceptual model. This research was conducted using a purposive sampling method and resulted in 41 companies as a sample of 80 property and real estate companies listed on the Indonesian Stock Exchange (IDX) in the 2016-2020 period, so that 205 observational data were obtained. In this study, to test the effect of the two predictive models of financial distress on firm value, it was tested through multiple regression analysis. The results of this study indicate that financial distress, both as measured by the Altman Z-score prediction model and the Zmijewski X-score prediction model, has a significant effect on firm value as reflected by the price book value (PBV). Even though the Zmijewski prediction model has a higher level of accuracy in predicting financial distress and its effect on firm value than the Altman Z-score prediction model.